2023
DOI: 10.3390/su15043115
|View full text |Cite
|
Sign up to set email alerts
|

Research Landscape of Adaptive Learning in Education: A Bibliometric Study on Research Publications from 2000 to 2022

Abstract: Adaptive learning is an approach toward personalized learning and places the concept of “learner-centered education” into practice. With the rapid development of artificial intelligence and other technologies in recent years, there have been many breakthroughs in adaptive learning. Thus, it is important to gain insight into the evolution of related research and to track the research frontiers to further promote its development. This study used CiteSpace and VOSviewer to conduct a bibliometric analysis of 644 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 104 publications
0
3
0
Order By: Relevance
“…Timezone maps drawn using CiteSpace are used to depict the changes in the development frontiers and hotspots over time and to determine the focus of research frontiers in specific periods. In educational research, bibliometric research based on CiteSpace and VOSviewer has demonstrated its unique advantages and application value [7][8][9].…”
Section: Methodsmentioning
confidence: 99%
“…Timezone maps drawn using CiteSpace are used to depict the changes in the development frontiers and hotspots over time and to determine the focus of research frontiers in specific periods. In educational research, bibliometric research based on CiteSpace and VOSviewer has demonstrated its unique advantages and application value [7][8][9].…”
Section: Methodsmentioning
confidence: 99%
“…Key initiatives in this direction include the development of adaptive learning platforms tailored to individual learning styles and pace, as discussed by Jing et al (2023) and Minn (2022), and social learning tools that encourage peer interaction and support, as noted by Barrot (2022). Additionally, acknowledging and accommodating cultural and educational background differences is crucial in adopting a “student‐learning” centric approach.…”
Section: Conclusion Findings and Prospectmentioning
confidence: 99%
“…Bubbles such as child, literacy, study, skill, and teacher are more prominent in Figure 8. Larger or darker bubbles usually indicate more important or frequently occurring keywords [77]; this allows researchers to understand that these terms have a higher level of interest in the literature.…”
Section: Co-occurrence Network Of Plmentioning
confidence: 99%